Detection of carcinoma micrometastases in bone marrow of dogs and cats using conventional and cell block cytology. (31st December 2012) - Taylor, Bonnie E.; Leibman, Nicole F.; Luong, Richard; Loar, Andrew S.; Craft, Diane M.
<x xml:space="preserve">Abstract</x> Background The presence of human breast carcinoma micrometastases in bone marrow is associated with poor overall survival, poor breast‐cancer‐specific survival, poor disease‐free survival, and poor distant disease‐free survival. In veterinary practice, the detection of micrometastases as a component of clinical staging is a routine practice for lymphomas and mast cell tumors, but not for carcinomas. Objectives This prospective study evaluated whether the identification of micrometastases from various carcinomas in dogs and cats in bone marrow using cell block cytology is technically feasible and whether it correlates with routine cytologic examination. Methods Thirteen dogs and 4 cats with various types of carcinomas were available for analysis. Routine and cell block cytologic evaluation combined with immunocytochemical staining with antibodies to CKAE1/AE3 and CK7 were performed on all bone marrow samples. Results Bone marrow micrometastasis was demonstrated by both methods in 2 dogs with advanced disease. In one case cells were immunoreactive for both CKAE1/AE3 and CK7. Conclusions This study demonstrates that cell block cytology is a practical and useful method for bone marrow evaluation and is suitable for cytokeratin immunocytochemical analysis.